Prospects for Digitalization of Energy and Agro-Industrial Complex of Kazakhstan - Smagulova, Sholpan; Yermukhanbetova, Aigerim; Akimbekova, Galiya; Yessimzhanova, Saira; Razakova, Dina; Nurgabylov, Murat; Zhakupova, Saltanat (International Journal of Energy Economics and Policy, 2022)
The goal is to conduct modeling and analyze the management efficiency of the energy industry and the agro-industrial complex based on the introduction of digitalization to stimulate economic growth in Kazakhstan. When writing the work, the following research methods were used - bibliometric, statistical, factorial, grouping and generalization, regression, comparative. Results - an economic assessment of the development of the electric power industry and the agro-industrial complex was carried out. It is noted that the economy of Kazakhstan is quite energy-intensive and costly. It is shown that the increasing level of agricultural production exceeds the demand for electricity consumption. The serious deterioration of electrical equipment and agricultural machinery has been identified, which is a barrier to the promotion of digital technologies. The stimulation of the growth of electricity generation from renewable energy sources based on the use of innovative and digital technologies is analyzed. The modeling of the development of the agro-industrial complex is carried out on the basis of the use of information, communication and digital technologies of smart farms on the example of the Almaty region. Presented and summarized measures for the implementation of innovative projects in digital energy and smart agriculture. The problems and recommendations are given for accelerating the implementation of digitalization in the energy sector and the agro-industrial complex. The role of digital and electronic technologies in agriculture and the energy complex in promoting the economic growth of Kazakhstan has been substantiated.